Acute and 24 h effect of kinesio taping on lower back muscle soreness during continued practice of cross-country skiing among collegiate students. A double-blind, randomized, placebo-controlled trial. - Merino-Marban, Rafael; Smuka, Ingrida; Romero-Ramos, Óscar; Fernández-Rodríguez, Emilio; Mayorga-Vega, Daniel (Taylor & Francis, 2021)
To examine the effects of kinesio taping on lower back muscle soreness immediately after its application and after 24 h during a cross-country skiing camp in collegiate students. The present study followed a double-blind, randomized, placebo-controlled trial design. Out of the 60 participants in a winter skiing camp, 54 volunteered to participate in the study (aged 21.3 years old, 20 females and 34 males). After 3 days of practical cross-country ski lessons (4 h per day), volunteers were, balanced by sex, randomly divided into three groups. One group had kinesio taping applied on the lower back, another had placebo tape applied and the third group nothing. The two-way ANOVA with the Bonferroni adjustment showed that the lower back muscle soreness levels in the kinesio taping group decreased statistically significantly from baseline to after 24 h of the kinesio taping application (p= 0.020). Kinesio taping reduced low back muscle soreness 24 h after its application produce by several days of cross-country skiing in physically active collegiate students. Kinesio taping method may be beneficial in reducing post-exercise delayed onset muscle soreness in healthy sport collegiate students.
Keywords: Mialgia; Cintas adhesivas; DOMS; Muscle pain; Elastic tape; Young adults; Skiers